2016
DOI: 10.1155/2016/6515069
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound Diagnostic Accuracy in Neonatal Pneumothorax

Abstract: Background. Pneumothorax (PTX) still remains a common cause of morbidity in critically ill and ventilated neonates. At the present time, lung ultrasound (LUS) is not included in the diagnostic work-up of PTX in newborns despite of excellent evidence of reliability in adults. The aim of this study was to compare LUS, chest X-ray (CXR), and chest transillumination (CTR) for PTX diagnosis in a group of neonates in which the presence of air in the pleural space was confirmed. Methods. In a 36-month period, 49 neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 17 publications
3
79
0
6
Order By: Relevance
“…Recently, a case report and two diagnostic accuracy studies suggest that LUS may also be very useful in the diagnosis of neonatal PNX. [33][34][35] In critically ill babies, LUS can be used for rapid detection of life-threatening tension PNX: an international multicentre study confirmed that LUS has an optimal diagnostic accuracy and is quicker than conventional radiology. 36 LUS also resulted more accurately than chest transillumination (which is also less accurate than conventional radiology).…”
Section: Meconium Aspiration Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a case report and two diagnostic accuracy studies suggest that LUS may also be very useful in the diagnosis of neonatal PNX. [33][34][35] In critically ill babies, LUS can be used for rapid detection of life-threatening tension PNX: an international multicentre study confirmed that LUS has an optimal diagnostic accuracy and is quicker than conventional radiology. 36 LUS also resulted more accurately than chest transillumination (which is also less accurate than conventional radiology).…”
Section: Meconium Aspiration Syndromementioning
confidence: 99%
“…36 LUS also resulted more accurately than chest transillumination (which is also less accurate than conventional radiology). 34 A case report described the use of LUS to detect and follow up neonatal interstitial emphysema. 37 No formal LUS description of neonatal pneumomediastinum exists.…”
Section: Meconium Aspiration Syndromementioning
confidence: 99%
“…Chest transillumination is commonly used to diagnose neonatal pneumothorax, although the sensitivity and specificity are inferior to chest X-ray. 7 One small study found the diagnostic accuracy of lung ultrasound similar to chest X-ray, 7 but widespread use of ultrasound at present is limited.…”
Section: Key Pointsmentioning
confidence: 99%
“…For these reasons, in many neonatal intensive care units (NICUs), LUS is replacing chest X-rays in diagnosing PTX due to its superior sensitivity and specificity [15][16][17] . Moreover, LUS has been shown to be more accurate than chest X-rays even for small, non-tension PTX 18,19,20,21,22,23,24,25,26,27 . LUS signs of PTX were first studied and described in adult critical patients.…”
Section: Introductionmentioning
confidence: 99%